Solve for c (4c+1)/2=(3c-2)/5

4c+12=3c-25
Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.
(4c+1)⋅5=2⋅(3c-2)
Solve the equation for c.
Simplify (4c+1)⋅5.
Apply the distributive property.
4c⋅5+1⋅5=2⋅(3c-2)
Multiply.
Multiply 5 by 4.
20c+1⋅5=2⋅(3c-2)
Multiply 5 by 1.
20c+5=2⋅(3c-2)
20c+5=2⋅(3c-2)
20c+5=2⋅(3c-2)
Simplify 2⋅(3c-2).
Apply the distributive property.
20c+5=2(3c)+2⋅-2
Multiply.
Multiply 3 by 2.
20c+5=6c+2⋅-2
Multiply 2 by -2.
20c+5=6c-4
20c+5=6c-4
20c+5=6c-4
Move all terms containing c to the left side of the equation.
Subtract 6c from both sides of the equation.
20c+5-6c=-4
Subtract 6c from 20c.
14c+5=-4
14c+5=-4
Move all terms not containing c to the right side of the equation.
Subtract 5 from both sides of the equation.
14c=-4-5
Subtract 5 from -4.
14c=-9
14c=-9
Divide each term by 14 and simplify.
Divide each term in 14c=-9 by 14.
14c14=-914
Cancel the common factor of 14.
Cancel the common factor.
14c14=-914
Divide c by 1.
c=-914
c=-914
Move the negative in front of the fraction.
c=-914
c=-914
c=-914
The result can be shown in multiple forms.
Exact Form:
c=-914
Decimal Form:
c=-0.6428571‾
Solve for c (4c+1)/2=(3c-2)/5

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top